Socialization on the Prevention of Underage Marriage, Sambik Bangkol Village, Gangga District, North Lombok Regency - Alawiyah, Tuti; Jayadi, Ahmad; Marwin, Marwin; Rivaldi, Dedi; Sari, Titik Puspa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The issue of early marriage is not new in Indonesia; it is a social problem that affects adolescents, with the majority of victims being young girls. In general, cases of underage marriage often occur in rural areas, and this frequently happens in families with low income, low education, and school dropouts. The world has made rapid progress in all fields, yet there are still many people who marry off their children at a young age, or more precisely, marry underage. Early marriage poses significant risks to the health of both mothers and children. The purpose of this community service is to provide education on early marriage in an effort to prevent underage marriage. The village of Sambik Bangkol in the Gangga District of North Lombok should be able to disseminate information about the impacts and issues of early marriage, as well as information to the wider community. The impact and issues of early marriage and community service are carried out through surveys, pretests, outreach with discussions and reviews, and discussions. The activity will take place in August 2024. This activity was attended by teenagers, middle school students, adults, and parents in Sambik Bangkol Village, Gangga District, North Lombok Regency.